Studying the Changes of Some Morphological Characteristics of Acanthobrama marmid (Heckel, 1843) in Tishreen Lake (Euphrates River) (Latakia University Journal -Biological Sciences Series, 2021)
Nineteen morphological characteristics were studied on 285 individuals of Acanthobrama marmid (Heckel, 1843) collected from Tishreen Lake (Euphrates River) during the period 9-4-2010 to 14-5-2012. All measurements: Standard Length (SL), Maximum Body Height (MAXH), Minimum Body Height (MINH), Caudal Peduncle Length (CPL), Pre Back Distance (PRB), Post Back Distance (POB), Dorsal Fin Length (DFL), Dorsal Fin Height (DFH), Pectoral Fin Length (PFL), Pectoral-Ventral Distance (PV), Anal Fin Length (AFL), Ventral-Anal Distance (VA), Head Length (HL) were calculated as a percentage of the Total length (TL), whereas the Snout Length (SnL), Cheek Length (CL), Between Eye Distance (BED), Head Height (HH), Eye Diameter (ED), were considered and compared to the head length. The results showed that seven morphometric characteristics were found to be genetically regulated and 12 affected by both the inheritance and ecology. It was also observed that approximately 18 morphometric traits showed a moderate correlation(0.90 > r) and only one a strong correlation (r > 0.90), and finally no sexual morphological differences between males and females of the studied species.